Pengaruh Electronic Word of Mouth dan Brand Ambassador Terhadap Brand Equity - Valentino Chandrawinata (Syntax Idea)
Brand equity is an intangible asset that can provide added value to the company. E-WOM (Electronic Word of Mouth) and brand ambassadors are two marketing strategies that can be used to increase brand equity. The purpose of this study was to analyze the effect of e-WOM and brand ambassadors on brand equity. This research uses quantitative methods. The data collection technique in this study was a literature study and a questionnaire. The population in this study were customers of Marhen J bags. The sampling technique in this study was random sampling technique. The data that has been collected is then analyzed using the help of the SPSS program. The results showed that E-WOM and brand ambassadors have a significant influence on the brand equity of Marhen J bag products.